Undergraduates' political participation behaviors in public universities of Hebei province, China - Yang, Yanan; Xia, Nan; Ahmad, Zaid; Jawan, Jayum; Talib, Ahmad Tarmizi (Canadian Center of Science and Education, 2018)
Political participation is a necessity of human life and the level of it reflects the degree of democracy which can be considered not only the right but also the obligation. Hebei province as a populous province has a large population of undergraduates, especially the expansion the university education policy carrying out in 2008. For the undergraduates in Hebei Province, they do not have adequate political knowledge, political skills and rarely practice in political activities. The objective of this article is to propose and evaluate students’ political participation behaviors in Hebei public universities of China. Data of this article is based on two sources; primary data were collected through questionnaire and 1990 informants were selected based on the cluster sampling method, the main statistical method for evaluation of research hypotheses is on the basis of on the basis of SmartPLS and SPSS software, meanwhile, secondary data which were collected from journal articles, reports and so on. Findings of this study indicate that, the level of students’ political participation was low in public universities in Hebei province in China. Moreover, the author elaborated four reasons that led to the low political participation behaviors in public universities of Hebei Province, which were the weak economic foundation, the backwardness of the cultural environment, the unsound political system and the influence of traditional culture. In addition, the author suggested that political participation among Hebei province public universities students need to improve and develop.